Making Cancer Visible: Unmasking Patients' Subjective Experiences. Issue 14 (6th December 2019) - Beach, Wayne A.
ABSTRACT: The Face of Cancer, an article and patient's painting published nearly 15 years ago, has contributed in significant ways to a body of research focusing on communication during oncology interviews. Impacts from this painting helped to create a sensitivity for analyzing naturally occurring video recordings, including moments when patients' subjective experiences are raised and responded to. Analysis begins with how a melanoma patient's facial expression bears striking resemblance to the painting, vocal and other visible social actions (e.g., gaze, gesture), and how patient's story about a friend's metastatic cancer reveals her primal fears and hopes about cancer. Actions displayed by other patients (breast, testicular, abdominal, and leukemia) are also examined to unmask how their faces and bodies make cancer visible, doctors' responses, and the complexities of how patients' stressful stories get constructed. Implications are raised for improving patient-provider relationships by offering more personalized care. Understanding how patients display their concerns and emotions, through spoken and embodied actions, enhances discernment about how best to provide tailored and supportive responses to patients' life-world experiences especially, but not exclusively, when dealing with the stresses and angst of cancer.